Tobacco smoking, associated risk behaviours, and experience with quitting: a qualitative study with homeless smokers addicted to drugs and alcohol - Garner, Laura; Ratschen, Elena (BioMed Central, 2013)
Background The prevalence of tobacco smoking among homeless people can reach more than 90%, with related morbidity and mortality being high. However, research in this area is scarce. This study aims to explore smoking and quitting related behaviours, experiences and knowledge in homeless smokers in the context of other substance abuse.